Do emotion-induced blindness and the attentional blink share underlying mechanisms? An event-related potential study of emotionally-arousing words. - MacLeod, Jeffrey; Stewart, Brandie; Newman, Aaron; Arnell, Karen (Cognitive, Affective & Behavioral Neuroscience, 2017)
When two targets are presented within approximately 500 ms of each other in the context of rapid serial visual presentation (RSVP), participants' ability to report the second target is reduced compared to when the targets are presented further apart in time. This phenomenon is known as the attentional blink (AB). The AB is increased in magnitude when the first target is emotionally arousing. Emotionally arousing stimuli can also capture attention and create an AB-like effect even when these stimuli are presented as to-be-ignored distractor items in a single-target RSVP task. This phenomenon is known as emotion-induced blindness (EIB). The phenomenological similarity in the behavioral results associated with the AB with an emotional T1 and EIB suggest that these effects may result from similar underlying mechanisms - a hypothesis that we tested using event-related electrical brain potentials (ERPs). Behavioral results replicated those reported previously, demonstrating an enhanced AB following an emotionally arousing target and a clear EIB effect. In both paradigms highly arousing taboo/sexual words resulted in an increased early posterior negativity (EPN) component that has been suggested to represent early semantic activation and selection for further processing in working memory. In both paradigms taboo/sexual words also produced an increased late positive potential (LPP) component that has been suggested to represent consolidation of a stimulus in working memory. Therefore, ERP results provide evidence that the EIB and emotion-enhanced AB effects share a common underlying mechanism.